Reducing Prominent Mandibular Angle Osteotomy Complications: 10-Year Retrospective Review. (December 2018) - Chen, Hongbo; Sun, Jiaming; Wang, Jiecong
Abstract : Background: Several methods are available for mandibular reduction, and each method is characterized by unique limitations and complications. However, only a few studies have systematically analyzed these complications. This study aimed to investigate the effects of the outcome of performing curved mandibular angle ostectomy and outer cortex grinding in 1-stage operation and to examine the causes of different types and characteristics of complications. Methods: The subjects consisted of 528 patients who were subjected to curved mandibular angle ostectomy and outer cortex grinding in 1-stage operation through an intraoral approach. Surgical complications and related factors were recorded, and the rates of complication according to surgeons were simultaneously evaluated. Results: The esthetic appearance of all of the patients was significantly improved, and they were satisfied with the results of the operation. The complication rate was 5.87%. No serious complications, such as subcondylar fracture, massive bleeding, permanent facial nerve, or asymmetry, occurred. Some complications, including 4 cases of hematoma, 4 cases of severe swelling, 2 cases of infection, and 1 case of sagging face, were detected. The absolute complication rate among faculty members ranged from 3.5% to 11.1%. Conclusions: Our protocol is an effective method for mandibular angle osteotomy with very few complications. The rate of complications can be effectively reduced, and some serious complications can be avoided because protective measures are improved.